2020
DOI: 10.1002/ctm2.97
|View full text |Cite
|
Sign up to set email alerts
|

A metagenomic study of biliary microbiome change along the cholecystitis‐carcinoma sequence

Abstract: Background Gallbladder cancer (GBC) is the most common cancer type of the biliary tract, and an association has been found between chronic calculous cholecystitis (CCC) and an increased incidence of GBC mortality. An understanding of the relationship between CCC and its carcinogenesis may enable us to prevent and cure GBC. In this study, we attempted to explore changes in the microbiome profile that take place during the transition from chronic cholecystitis mucosa to malignant lesions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Based on the analysis of the great number of contradictory results reported in the literature, it is currently difficult to associate specific microbial signatures or the Firmicutes/Bacteroidetes ratio with determining health status and more specifically to consider it as a hallmark of GSD and/or obesity. However, most authors believe that both obesity [ 33 , 34 , 40 , 48 , 64 , 130 ] and GSD [ 5 , 6 , 81 , 103 , 109 , 111 , 117 , 118 , 119 , 120 ] are associated with reduced microbial diversity.Therefore, it is important to look at the overall composition of the gut microbial population structure as an indicator of obesity and obesity-associated pathologies, such as GSD, rather than simply the Firmicutes/Bacteroidetes ratio [ 150 ]. However, in my opinion, it is possible to modify this ratio, e.g., to introduce a coefficient that characterizes BMI, to calculate the ratio not of the Firmicutes phylum, but only of the Clostridia class, and so on.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the analysis of the great number of contradictory results reported in the literature, it is currently difficult to associate specific microbial signatures or the Firmicutes/Bacteroidetes ratio with determining health status and more specifically to consider it as a hallmark of GSD and/or obesity. However, most authors believe that both obesity [ 33 , 34 , 40 , 48 , 64 , 130 ] and GSD [ 5 , 6 , 81 , 103 , 109 , 111 , 117 , 118 , 119 , 120 ] are associated with reduced microbial diversity.Therefore, it is important to look at the overall composition of the gut microbial population structure as an indicator of obesity and obesity-associated pathologies, such as GSD, rather than simply the Firmicutes/Bacteroidetes ratio [ 150 ]. However, in my opinion, it is possible to modify this ratio, e.g., to introduce a coefficient that characterizes BMI, to calculate the ratio not of the Firmicutes phylum, but only of the Clostridia class, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…During a cholecystectomy, mucosal DNA extraction and metagenomic sequencing were performed to evaluate changes in the microbiota between chronic calculous cholecystitis and gallbladder cancer patients [ 118 ]. At the phylum level, Firmicutes , Bacteroidetes , Actinobacteria , and Proteobacteria were found to be stable in both groups.…”
Section: The Firmicutes/bacteroidetesratio and Gsdmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to date, few studies characterised the human biliary metagenome. Song et al [2], performed metagenomic sequencing of the biliary microbiota of individuals who had undergone laparoscopic cholecystectomy or radical cholecystectomy. Shen et al [3], reported metagenomic characterisation of bile samples from patients with gallstone disease.…”
Section: Introductionmentioning
confidence: 99%